CURRENT STATUS OF COCONUT RESEARCH IN SRI LANKA - RANJITH MAHINDAPALA (International Coconut Community, 1991)
Coconut occupies about 410,000 ha of land in Sri Lanka, and is the largest plantation crop. The most important coconut growing area is called the